Percutaneous balloon compression of trigeminal ganglion under conscious sedation local anesthesia for the treatment of primary trigeminal neuralgia—A prospective cohort study - Zhi, Dou; Guo, Yuna; He, Liangliang; Yang, Liqiang (Frontiers in Neurology, 2023)
Introduction Trigeminal neuralgia is a debilitating condition that can significantly impair the quality of life of affected individuals. Percutaneous balloon compression (PBC) has been established as an effective treatment for this condition. However, the use of general anesthesia during the procedure poses challenges to achieving the desired degree of nerve damage without causing excessive numbness. In this study, we aimed to evaluate the feasibility and efficacy of performing PBC under conscious sedation of local anesthesia. Methods We improved the surgical procedure for PBC by administering intraganglionic lidocaine 0.2% with fine needle aspiration to achieve conscious sedation. This allowed the operator to determine the degree of nerve damage in real time through the tactile test. We conducted a clinical observation of 87 patients who underwent PBC under conscious sedation of local anesthesia. We evaluated the intraoperative blood pressure and heart rate changes, postoperative facial pain relief, and occurrence of complications such as severe facial numbness, irreversible keratitis, vision loss, and masticatory muscle weakness. Results All 87 patients achieved immediate relief of facial pain after undergoing PBC under conscious sedation of local anesthesia. The intraoperative blood pressure and heart rate changes were <20% of the baseline value. No patient experienced severe facial numbness or developed irreversible keratitis, vision loss, or masticatory muscle weakness. Discussion Our findings suggest that PBC under wide-awake local anesthesia is a safe and effective treatment for trigeminal neuralgia. The use of conscious sedation of local anesthesia during the procedure allows the operator to achieve the desired degree of nerve damage without causing excessive numbness. This can lead to long-term pain relief and improved quality of life for patients with trigeminal neuralgia.